Tax Workers and Private Entrepreneurs in the Urals as Actors of the NEP Economy: Following the “Astrakhan Case” - Kilin, A. P. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2016)
The article analyzes materials of a legal case initiated as a result of bribery and fraud committed by workers of the Sverdlovsk district and the Ural regional financial departments and private traders in Sverdlovsk in 1929. Referring to regional documents, the author considers the all-Russian campaign which started with the so-called “Astrakhan case” and aimed at the abolition of private capitalist economic structures in the economy. The aim of research is to examine the interaction between private entrepreneurs and the staff of financial agencies in the late 1920s that are regarded as actors of entrepreneurial activity during the NEP. The subject of the research is the parties’ interests, the nature of the interaction between the employees of the fiscal authorities and private entrepreneurs. The chronological framework (1928–1929) is predetermined by the “Astrakhan” and “Sverdlovsk” lawsuits. Based on the actor model, the author considers the parties’ interests as actors of economic activity, motives of their behavior, problems of interaction between private entrepreneurs and employees of financial authorities; reasons for which the staff of the fiscal authorities sabotaged the process of the forced liquidation of private owners; the role of the judicial process in the justification of the elimination of district division within Ural Region.